Kinetic properties of separated solid-liquid fractions of blended swine waste slurry. - Bedaño, Jose Ali F. Ph.D (Philippine Engineering Journal)
The kinetic properties ultimate methane yield (bo) and substrate inhibition coefficient (K) of separated solid-liquid fractions of blended surface scaped swine waste were evaluated from data on batch digestion and semicontinuous high-rate digestion. Results showed that the solid fraction had a lower Bo (0.373 Ii CII4/gm VS added) than the liquid fraction (0.498 Ii CH4/gm VS added) due to its higher concentration of refractory materials. K was evaluated using Chen & Hashimoto's model for continuous well mixed anaerobic systems at steady state. The relationship between influent substrate concentration (So) and K was found to be exponential. Empirical algorithms derived at different combinations of organic loading rate (OLR), Hydraulic retention time (HRT) and temperature are as follows : Solid Fraction : K = 0.429 + 0.00177 exp (0.187 So), r2 = 0.997 Liquid Fraction : K=0.798 + 9.43 x 10 -8 exp (1.808 So), r2=0.863 The threshold substrate concentration where inhibition might start was approximately 30 gm VS/Ii for the solid fraction and 8 gm VS/Ii for the liquid fraction.